2016
DOI: 10.7861/clinmedicine.16-3-294
|View full text |Cite
|
Sign up to set email alerts
|

Lesson of the month 2: Houssay phenomenon – hypopitutarism leading to remission of diabetes

Abstract: Because of a pituitary insult and the subsequent loss of counter-regulatory hormones, individuals can experience increased sensitivity to insulin, hypoglycaemia or even complete amelioration of diabetes; this is known as the Houssay phenomenon. Severe dehydration following diarrhoea can lead to pituitary infarction causing hypopituitarism. We describe this situation in a patient with insulin-treated type-2 diabetes presenting with recurrent hypoglycaemia and cessation of insulin requirement along with weight l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(11 reference statements)
0
3
2
Order By: Relevance
“…Several studies showed that panhypopituitarism due to pituitary hemorrhage/infarction (including Sheehan's syndrome) induced a remarkable reduction of insulin doses in patients with type 1 diabetes [3,4,13,14]. A complete amelioration of diabetes induced by adrenal insufficiency was reported in patients with type 2 diabetes [5], but it has never been reported in a patient with type 1 diabetes with decreased insulin secretory capacity to an insulindependent level as observed in our patient.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Several studies showed that panhypopituitarism due to pituitary hemorrhage/infarction (including Sheehan's syndrome) induced a remarkable reduction of insulin doses in patients with type 1 diabetes [3,4,13,14]. A complete amelioration of diabetes induced by adrenal insufficiency was reported in patients with type 2 diabetes [5], but it has never been reported in a patient with type 1 diabetes with decreased insulin secretory capacity to an insulindependent level as observed in our patient.…”
Section: Discussioncontrasting
confidence: 51%
“…Glucocorticoids increase blood glucose levels by increasing hepatic gluconeogenesis and inhibiting the uptake and utilization of glucose in peripheral tissues. Glucocorticoid deficiency can lead to an amelioration of glycemic control and/or a reduction of the insulin dose in patients with diabetes [2][3][4][5], but it is unclear whether the hyperglycemia in type 1 diabetes could be ameliorated without insulin treatment when complicated with adrenal insufficiency. Here, we describe the case of a patient who latently developed type 1 diabetes with endogenous insulin deficiency concurrently with adrenal insufficiency due to autoimmune hypophysitis.…”
Section: Adrenocorticotropic Hormone (Acth)mentioning
confidence: 99%
“…Several studies showed that panhypopituitarism induced a remarkable reduction in insulin doses in patients with T1DM [ 22 , 23 ]. A complete amelioration of diabetes induced by adrenal insufficiency was reported in patients with type 2 diabetes [ 24 ], but it has never been reported in a patient with T1DM with decreased insulin secretory capacity to an insulin-dependent level as observed in our patient.…”
Section: Discussioncontrasting
confidence: 50%
“…Hypopituitarism could lead to recurrent hypoglycemia in diabetic patients and to a reduction in their insulin requirements as a result of adrenocorticotropic hormone deficiency (the Houssay phenomenon). [3,4] Obscure recurrent hypoglycemia requires endocrinologic tests to clarify possible underlying hypocortisolism. [5]…”
Section: Discussionmentioning
confidence: 99%